Bust : Greece, the Euro, and the sovereign debt crisis - Lynn, Matthew (Hoboken, N.J. : Bloomberg Press, 2011)
"Athens, Greece May Day 2010. The International Monetary Fund (IMF) and the European Union (EU) were putting together the final details of a 100-billion Euro rescue package for the country. The Greek Prime Minister, George Papandreou had agreed to a savage package of Austerity Measures involving cuts in public spending and lower salaries and pensions. Outside, riot police were deployed as protestors gathered to fight the austerity program. A country with a history of revolution and dictatorship hovered on the brink of collapse with the world's financial markets watching to see if the deal cobbled together would be enough to both calm the markets, rescue the Greek economy, and with it the Euro, from oblivion. In Bust: Greece, the Euro, and the Sovereign Debt Crisis leading market commentator Matthew Lynn blends financial history, politics and current affairs to tell the story of how one nation rode the wave of economic prosperity and brought a continent, a currency, and potentially, the global financial system to its knees. Bust: Greece, the Euro, and the Sovereign Debt Crisis is a story of government deceit, unfettered spending, and cheap borrowing. As well as charting Greece?s rise, and spectacular fall from grace, it looks at the global repercussions of a financial disaster that shows many of the hallmarks of the Lehman Brother's debacle. It looks at how the Greek contagion has spread like wildfire through Europe, and, as the global financial community looks on in concern, club Med, or PIGGS countries succumb to its influence. And of course, no financial crisis is complete without Goldman Sachs and murky deals, as the author explores how speculators and derivatives traders compounded the problem. Written in a lively and entertaining style, Bust: Greece, the Euro, and the Sovereign Debt Crisis is a lively and engaging account of a country gone wrong, for anyone interested in world events and global economics."--
"Written in a lively and entertaining style, Bust: Greece, the Euro, and the Sovereign Debt Crisis is a lively and engaging account of a country gone wrong, for anyone interested in world events and global economics"--
Includes bibliographical references (p. 263-271).
nmn 12/10/17
Loan
Keywords: Financial crises; Debts, External; Economic stabilization; Economic policy; Economic conditions; Greece